PERTANGGUNGJAWABAN PIDANA LETNAN KOLONEL UNTUNG DALAM TINDAK PIDANA MAKAR PADA PERISTIWA GERAKAN 30 SEPTEMBER 1965 - Wan Ferry Fadli; Erdianto '; Mexsasai Indra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
In running the government, a state not escape from the disruption of sovereignty, whether from the outside, as well as from within the country itself. One real nuisance is a threat to the security of a country. Crimes againts state security, or often referred to as treason, is an act which aimed to destroy, overthrow, or take over the administration of the specific reasons. One plot events that occurred in Indonesia is in motion the events of September 30 in 1965 movement (G30S). One of the key figures in the G30S is a Lieutenant Colonel Untung. Purpose of this thesis, namely : first, criminal responsibility of Lieutnant Colonel Untung in the crime treason on G30S. Second, the application of the crime of treason chapter in the trial of Lieutenant Colonel Untung is appropriate or not yet. This type of research is normative juridical, who performed with the approach to find the law to a case in concerto, which approaches seek how to find the relevant facts, and then find the law in abstracto the right to object at carefully. Data sources used include primary data, secondary data, and the data tertiary. Data collection techniques using literature study. Of the research problem, there are two main things that can be concluded. First, if we dissect the action of the elements that can be accounted for, Lieutenant Colonel Untung criminal liability can be requested on he did in the crime of treason in G30S. Second, in the proceedings of Lieutenant Colonel Untung, the judges stated that he is guilty of committing criminal offenses including Article 107 Paragraph 2, Article 108 Paragraph 2, Article 110, of the Criminal Code (KUHP) and Article 2 of The Presidential Edict No. 5 In 1959. Suggentions author, first, improve the national judicial system to be more balanced between the rule of law and sense of justice. Second, straighten the actual history based on facts for the sake of future generations it is necessary to know the actual history as a guide and learning in the future.Keyword : Crime of Responsibility – Treason – September 30 in 1965 Movement